NITER-SiCf / SiC ceramic-based composite material and preparation method thereof
By using rare earth silicon carbon coated SiC powder as the initial material, combined with the slurry preparation, interface deposition and hot press sintering processes, the oxidation and erosion of SiCf/SiC ceramic matrix composites in high-temperature environments is solved, and low-temperature preparation and high-performance materials are achieved.
Patent Information
- Application Number
- CN202411919408.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
SiCf/SiC ceramic matrix composite materials are susceptible to erosion and oxidation of fuel gas in high-temperature environments, resulting in erosion between fibers and interfaces. The high-temperature and high-pressure conditions of traditional preparation methods are prone to damage the fibers and interfaces.
SiC@RE3Si2C2 powder coated with SiC with rare earth (RE) silicon carbon (RE3Si2C2) is used as the initial slurry powder. SiCf/SiC ceramic matrix composite materials are prepared through slurry preparation, interface deposition, vacuum impregnation, cut lamination and hot press sintering processes to reduce the sintering temperature and reduce the thermochemical damage between the fiber and the interface.
The low-temperature preparation of SiCf/SiC ceramic matrix composite materials with high density and high crystallinity of the matrix is achieved, which improves the mechanical properties and temperature resistance of the material, reduces the sintering temperature and fiber damage, and extends the service temperature and life of the material.
Smart Images

Figure CN119661244A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to SiC f / SiC ceramic matrix composite material preparation technology field, relates to a SiC f / SiC ceramic-based composite material and preparation method thereof, specifically relating to a method for preparing SiC based on nano-slurry impregnation and hot pressing sintering f / SiC ceramic matrix composites. Background Art
[0002] As aircraft engines develop towards a high thrust-to-weight ratio, the operating temperature of their hot end components is gradually increasing. The average turbine pre-turbine temperature of aircraft engines with a thrust-to-weight ratio of 12 to 15 that are being developed will exceed 1800°C, far exceeding the temperature that traditional nickel-based high-temperature alloys can withstand. It is urgent to develop new high-temperature resistant structural materials for hot end components. Continuous silicon carbide fiber reinforced silicon carbide ceramic matrix composites (SiC f / SiC) has the advantages of low density, wear resistance, high specific strength, high specific modulus, high temperature resistance and non-brittle fracture, and is regarded as an important candidate material for the hot end components of the new generation of aircraft engines.
[0003] SiC f / SiC ceramic matrix composites face the challenges of fuel gas erosion and oxidation during service. In particular, the oxidation of the internal fibers and interfaces of the material has a great impact on the performance of the composite material. f The internal pores of SiC ceramic matrix composites provide channels for the diffusion of oxidizing gases, further accelerating the f / SiC composite fiber and interface erosion.
[0004] Nano-impregnation eutectic liquid phase sintering (NITE) is a method of impregnating SiC fibers with nano-slurry SiC and then sintering dense composite materials by hot pressing. Products produced by the NITE method can take into account high density, high crystallinity and a near-stoichiometric ratio of the SiC matrix, which gives it excellent high-temperature oxidation resistance. However, its preparation temperature is often high (≥1800°C), and the pressure is high (≥15MPa). The fibers and interfaces are easily damaged during the synthesis process, and the technical requirements are high. Summary of the invention
[0005] In view of the above problems, the present invention provides a high-density, high-crystallinity SiC f / SiC ceramic matrix composite material and low temperature preparation method thereof. Specifically, SiC@RE3Si2C2 powder of SiC coated with rare earth (RE) silicon carbon (RE3Si2C2) is used as the initial slurry powder of the material, SiC fiber is used as the reinforcing fiber, and SiC is prepared through slurry preparation, interface deposition, vacuum impregnation, cutting and lamination, and hot pressing sintering processes. f / SiC ceramic matrix composite materials.
[0006] In one aspect, the present invention provides a NITE-SiC f The preparation method of the NITE-SiC ceramic matrix composite material comprises: powder preparation, SiC fiber weaving, slurry impregnation and hot pressing sintering to obtain the NITE-SiC f / SiC ceramic matrix composites; The powder is prepared by: in-situ growing a RE3Si2C2 coating layer on the surface of SiC powder by a molten salt method to obtain SiC@RE3Si2C2 powder of SiC coated with RE3Si2C2; the molten salt method comprises: taking a rare earth metal element powder or a rare earth metal hydride as a raw material, mixing it with SiC powder and molten salt, and synthesizing it to obtain the SiC@RE3Si2C2 powder of SiC coated with RE3Si2C2; The slurry impregnation is as follows: SiC@RE3Si2C2 powder is mixed with a mixed solution to prepare SiC@RE3Si2C2 impregnation slurry, and then the SiC fiber braid is immersed in the SiC@RE3Si2C2 impregnation slurry.
[0007] In the present invention, SiC@RE3Si2C2 powder of SiC coated with rare earth (RE) silicon carbon (RE3Si2C2) is used as the initial slurry powder, SiC fiber is used as the reinforcing fiber, and SiC is prepared through slurry preparation, interface deposition, vacuum impregnation, cutting and lamination, and hot pressing sintering. f / SiC ceramic-based composite materials. Among them, RE3Si2C2 is used as a liquid-phase sintering aid in the sintering process of SiC materials. It can react with SiC at a temperature below 1600°C to form a low-temperature liquid phase to promote the sintering mass transfer process. Compared with the traditional oxide sintering aid RE3Si2C2, it can reduce the densification temperature to a certain extent. Growing it directly on the surface of SiC powder is conducive to the formation and uniform dispersion of the liquid phase, and promotes the low-temperature sintering process. Using SiC fiber as the reinforcing fiber can improve the toughness of the material and make it have non-brittle fracture properties. In addition, this method uses SiC@RE3Si2C2 powder as the initial powder for the preparation of the composite material, which can reduce NITE-SiC f / SiC composite materials, reduce the sintering energy barrier, lower the material preparation temperature, reduce high-temperature thermal damage and chemical damage during the preparation of SiC fibers, and improve the overall performance of the composite materials.
[0008] Preferably, the rare earth metal single substance powder is at least one of Pr powder, Gd powder, Y powder and Ho powder; The rare earth metal hydride is at least one of PrH3, GaH2, and YH2; The molten salt is at least two of NaCl, KCl, LiCl, Na2SO4, and K2SO4; preferably, the molten salt is mixed in an atomic ratio of 1:1; The synthesis temperature of the molten salt method is 750-1100° C. and the time is 2-10 hours.
[0009] Preferably, the particle size of the rare earth metal powder or rare earth metal hydride is 0.5 to 500 μm; the particle size of the SiC powder is 40 to 10000 nm; the thickness of the RE3Si2C2 coating layer is 10 to 2000 nm; the total particle size of the SiC@RE3Si2C2 powder is 50 to 12000 nm; Preferably, the atomic ratio of the rare earth metal element powder or rare earth metal hydride to SiC powder is 1:(2-25).
[0010] Preferably, the mass ratio of the total mass of the rare earth metal powder or rare earth metal hydride and SiC powder to the molten salt is 1:(3-8).
[0011] Preferably, the SiC@RE3Si2C2 powder is mixed with a mixed solution to obtain a SiC@RE3Si2C2 impregnation slurry; wherein the mixed solution comprises a dispersant, a binder, a plasticizer and a solvent; The dispersant is polyvinyl pyrrolidone, polyethylene imine, tetramethyl ammonium hydroxide, fish oil or castor oil; the binder is polyvinyl butyral or polyvinyl alcohol; the plasticizer is polyethylene glycol, dibutyl phthalate or butyl benzyl phthalate; the solvent is deionized water, anhydrous ethanol, xylene or isopropanol; Preferably, the mass ratio of the SiC@RE3Si2C2 powder, dispersant, binder, plasticizer and solvent is 1: (0.01-0.1): (0.01-0.2): (0.005-0.5): (2-10); more preferably, it is 1: (0.01-0.1): (0.01-0.1): (0.005-0.25): (2-10).
[0012] Preferably, the solid content of the SiC@RE3Si2C2 impregnation slurry is 30% to 55%.
[0013] Preferably, the raw materials are mixed by ball milling; the parameters of the ball milling include: a ball milling speed of 120 to 400 r / min, a ball milling time of 4 to 24 h, and a ball-to-material ratio of (1 to 5):1.
[0014] Preferably, SiC fibers are woven to obtain the SiC fiber woven body; preferably, the SiC fibers are continuous SiC fibers with a diameter of 5 to 20 μm; the SiC fibers are woven in a unidirectional winding, 2D weaving, 2.5D weaving or 3D weaving manner.
[0015] Preferably, the interface layer is deposited on the surface of the SiC fiber braid by chemical vapor deposition; wherein the interface layer includes a single-layer interface phase or a multi-layer interface phase; preferably, the single-layer interface phase is at least one of a pyrolytic carbon interface, a BN interface, and a SiC interface; the multi-layer interface phase is (PyC-SiC) n 、(BN-SiC) n 、(BN-PyC) n At least one of; More preferably, the thickness of the interface layer is 100 to 1500 nm; Preferably, the conditions of the chemical vapor deposition method include: a deposition temperature of 800 to 1300° C., a gas pressure of 1 to 30 kPa, and a deposition time of 0.5 to 5 h; depending on the type of interface layer, the reaction gas includes methane, ethane, ethylene, propylene, boron trichloride, ammonia, methyltrichlorosilane, and the flow rate is 5 to 50 mL / min; the dilution gas and carrier gas are hydrogen or argon hydrogen, and the flow rate is 50 to 200 mL / min.
[0016] Preferably, the SiC fiber braid is immersed in the SiC@RE3Si2C2 impregnation slurry, and dried to obtain a SiC@RE3Si2C2 fiber preform; the impregnation method of the SiC fiber braid includes vacuum impregnation, vibration impregnation, pressure impregnation, ultrasonic impregnation, ultrasonic-assisted vacuum impregnation or vibration-assisted vacuum impregnation; the impregnation time is 10 min to 3 h, preferably 10 min to 2 h; The drying method is atmospheric pressure drying or vacuum drying; preferably, the drying temperature is 40 to 90° C. and the drying time is 5 to 20 hours.
[0017] Preferably, the obtained SiC@RE3Si2C2 fiber preform is laminated and hot-pressed to obtain the NITE-SiC f / SiC ceramic-based composite material; the hot pressing sintering parameters include: sintering temperature of 1300-1700°C, sintering pressure of 5-50MPa, and sintering time of 0.5-4h.
[0018] On the one hand, the present invention provides a NITE-SiC prepared according to the above preparation method f / SiC ceramic matrix composite material, the NITE-SiC f / In SiC ceramic matrix composite materials, the volume fraction of SiC fiber is 20-70%; The NITE-SiC f The volume density of SiC ceramic matrix composite material is 2.9~3.8g / cm 3 ; The NITE-SiC f The open porosity of the SiC ceramic matrix composite material does not exceed 4%, preferably does not exceed 3%; The NITE-SiC f The flexural strength of SiC ceramic matrix composite materials is 150-800 MPa.
[0019] In the present invention, a RE3Si2C2 layer is constructed on the surface of SiC powder to replace the original rare earth oxide sintering aid. During the sintering process, the SiC material can quickly form a eutectic liquid phase with RE3Si2C2 at a lower temperature, which significantly improves the material propagation process of the SiC material during low-temperature sintering, thereby improving the SiC f / SiC materials can be sintered at low temperature to achieve high density, lower the sintering temperature, reduce the thermal chemical damage to the fiber and interface during the material preparation process, and improve the overall performance of the material.
[0020] Beneficial effects: (1) NITE-SiC prepared by the present invention f / SiC ceramic matrix composites have excellent mechanical properties and temperature resistance; (2) NITE-SiC provided by the present invention f The preparation method of the NITE-SiC ceramic matrix composite material has the advantages of short synthesis cycle and mild preparation conditions, and can reduce the thermal damage of fibers and interfaces during sintering. f The preparation method of SiC ceramic-based composite materials can reduce the sintering temperature by 200 to 500°C, reduce the thermal damage of the composite fiber during the sintering process, and increase the service temperature and life of the material in an oxidizing environment. It has good application prospects in high-tech fields such as hot end components of aerospace vehicles and nuclear reactors. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a morphology picture of SiC@Pr3Si2C2 powder of Pr3Si2C2 coated SiC prepared by the present invention; Figure 2 Preparation of NITE-SiC for Example 1 of the present invention f SEM image of polished cross-section morphology of / SiC ceramic matrix composite; Figure 3 NITE-SiC prepared in Example 1 of the present invention f Load-displacement curve of / SiC ceramic matrix composites; Figure 4 NITE-SiC prepared in Example 1 of the present invention f XRD pattern of / SiC ceramic matrix composites; Figure 5 NITE-SiC prepared in Comparative Example 2 f SEM image of polished cross-section morphology of / SiC ceramic matrix composite; Figure 6 NITE-SiC prepared in Comparative Example 2 f Load-displacement curve of / SiC ceramic matrix composites. DETAILED DESCRIPTION
[0022] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0023] The present invention provides a NITE-SiC f The invention discloses a method for preparing a SiC / SiC ceramic matrix composite material, wherein SiC@RE3Si2C2 powder of SiC coated with rare earth (RE) silicon carbon (RE3Si2C2) is used as the initial slurry powder of the material, and SiC fiber is used as the reinforcing fiber. After slurry preparation, fiber weaving, interface deposition, slurry impregnation and hot pressing sintering, a NITE-SiC with high density, high thermal conductivity, high matrix crystallinity and near stoichiometric ratio is obtained. f / SiC composite material. The method can reduce the sintering temperature by 200-500°C, reduce the thermal damage of the composite fiber during the sintering process, and increase the service temperature and life of the material in an oxidizing environment. It has good application prospects in high-tech fields such as hot end components of aerospace vehicles and nuclear reactors. The NITE-SiC prepared by the present invention f / SiC ceramic matrix composites have excellent mechanical properties and temperature resistance.
[0024] In the present invention, RE3Si2C2 replaces the traditional NITE-SiC f / SiC preparation process of rare earth oxide sintering aid, compared with the rare earth oxide and SiO2 reaction to form a liquid phase, RE3Si2C2 can directly react with SiC eutectic, its liquid phase formation temperature is lower, the mass transfer efficiency is higher, thereby reducing the material densification required sintering temperature. NITE method for composite material preparation fiber temperature resistance requirements, improve NITE-SiC f / SiC material properties.
[0025] The following is an exemplary description of the NITE-SiC provided by the present invention. f Preparation method of SiC ceramic matrix composite material.
[0026] Preparation of SiC@RE3Si2C2 powder of SiC coated with RE3Si2C2. The present invention in situ grows a RE3Si2C2 coating layer on the surface of SiC powder by a molten salt method. The raw material powder and molten salt are mixed in a glove box and placed in an alumina crucible, and then the mixed powder is heated to the target temperature in an inert atmosphere muffle furnace and kept warm. Through the reaction: 3RE+2SiC→RE3Si2C2, a layer of RE3Si2C2 coating layer is in situ grown on the surface of SiC powder. Subsequently, it is repeatedly dissolved, filtered and dried with deionized water to obtain SiC@RE3Si2C2 coated SiC powder. It should be noted that (1) the raw material mixing and sintering processes in the preparation process of SiC@RE3Si2C2 powder need to be carried out in an inert atmosphere to prevent the oxidation of rare earth elements or rare earth hydrides. (2) After the molten salt reaction, the dissolution of the molten salt can be assisted by ultrasound or mechanical stirring. Filter after the dissolution is completed. Repeat this step 3 to 10 times until the filtered liquid cannot discolor the silver nitrate solution, proving that the molten salt is completely removed. (3) Drying of the filtered powder is performed by low-temperature vacuum drying at a temperature of 40 to 80°C for 5 to 24 hours.
[0027] In an optional embodiment, the raw material powder is a rare earth metal powder or a rare earth metal hydride, SiC powder and molten salt; wherein the rare earth metal powder is at least one of Pr powder, Gd powder, Y powder, Ho powder and Y powder; the rare earth metal hydride is at least one of PrH3, GaH2 and YH2. The molten salt is at least two of NaCl, KCl, LiCl, Na2SO4 and K2SO4; preferably, the molten salt is mixed in a ratio of 1:1.
[0028] In an optional embodiment, the particle size of the rare earth metal single substance powder or rare earth metal hydride is 0.5-500 μm. Smaller particle size is conducive to uniform mixing, faster dissolution in molten salt and uniform deposition on the surface of SiC powder.
[0029] In an optional embodiment, the particle size of the SiC powder is 40 to 10000 nm. Smaller powders make the formed SiC@RE3Si2C2 powder have a smaller particle size, which is conducive to the subsequent slurry to be better impregnated into the fiber bundle.
[0030] In an optional embodiment, the atomic ratio of the rare earth metal powder or rare earth metal hydride to SiC powder is 1:(2-25); the mass ratio of the total mass of the rare earth metal powder or rare earth metal hydride and SiC powder to the mass ratio of the molten salt is 1:(3-8).
[0031] In an optional embodiment, the synthesis temperature of the molten salt method is 750-1100° C. and the time is 2-10 h.
[0032] Preparation of impregnation slurry: The SiC@RE3Si2C2 powder prepared in the above steps, the dispersant, the binder, the plasticizer and the solvent are mixed to obtain the SiC@RE3Si2C2 impregnation slurry.
[0033] In the present invention, RE3Si2C2 is used as a liquid phase sintering aid in the sintering process of SiC material, and can react with SiC to form liquid phase assisted sintering at a temperature below 1600°C. Compared with traditional oxide sintering aids, RE3Si2C2 can reduce the sintering temperature to a certain extent, and growing it directly on the surface of SiC powder is conducive to the formation and uniform dispersion of the liquid phase, thereby promoting sintering.
[0034] In an optional embodiment, the dispersant is polyvinyl pyrrolidone, polyethylene imine, tetramethyl ammonium hydroxide, fish oil or castor oil. The binder is polyvinyl butyral or polyvinyl alcohol. The plasticizer is polyethylene glycol, dibutyl phthalate or butyl benzyl phthalate. The solvent is deionized water, anhydrous ethanol, xylene or isopropanol.
[0035] In an optional embodiment, the mass ratio of the SiC@RE3Si2C2 powder, dispersant, binder, plasticizer, and solvent is 1: (0.01-0.1): (0.01-0.2): (0.005-0.5): (2-10), preferably 1: (0.01-0.1): (0.01-0.1): (0.005-0.25): (2-10). The present invention controls the viscosity and solid content of the slurry by regulating the mass ratio of each raw material, thereby affecting the effect of the slurry impregnation process. If the slurry viscosity is too high, it will be difficult to immerse into the fiber bundle, and if the slurry solid content is too low, it will also affect the impregnation effect of the slurry.
[0036] In an optional embodiment, the mixing method of the raw materials can be roller ball milling, planetary ball milling, or magnetic stirring. Preferably, the mixing method is ball milling mixing (planetary ball milling); the parameters of the ball milling mixing include: the ball milling speed is 120-400r / min, the ball milling time is 4-24h, and the ball-to-material ratio is (1-5):1. Preferably, the SiC@RE3Si2C2 powder and the dispersant are mixed for the first ball milling, and then the binder and the plasticizer are added for the second ball milling to obtain the SiC@RE3Si2C2 impregnation slurry. More preferably, the speed of the first ball milling is 120-400r / min, and the ball milling time is 4-24h; the speed of the second ball milling is 120-400r / min, and the ball milling time is 4-24h. Among them, the first ball milling can ensure that the nano powder is fully dispersed; the second ball milling after adding the binder and the plasticizer can better improve the shaping of the slurry. Therefore, the present invention adopts two ball millings to make the slurry have better comprehensive performance.
[0037] The SiC fibers are braided to obtain a SiC fiber braided body.
[0038] In an optional embodiment, the SiC fiber is a continuous SiC fiber with a diameter of 5 to 20 μm. The SiC fiber is woven in a unidirectional winding, 2D weaving, 2.5D weaving or 3D weaving manner.
[0039] The interface layer is deposited on the surface of the SiC fiber braid by chemical vapor deposition.
[0040] In an optional embodiment, the interface layer includes a single-layer interface phase or a multi-layer interface phase; preferably, the single-layer interface phase is at least one of a pyrolytic carbon interface, a BN interface, and a SiC interface; the multi-layer interface phase is (PyC-SiC) n 、(BN-SiC) n 、(BN-PyC) n At least one of; More preferably, the thickness of the interface layer is 100 to 1500 nm;
[0041] The conditions of the chemical vapor deposition method include: a deposition temperature of 800 to 1300° C., a gas pressure of 1 to 30 kPa, and a deposition time of 0.5 to 5 hours; depending on the type of interface layer, the reaction gas includes methane, ethane, ethylene, propylene, boron trichloride, ammonia, and methyltrichlorosilane, with a flow rate of 5 to 50 mL / min; the dilution gas and carrier gas are hydrogen and argon hydrogen, with a flow rate of 50 to 200 mL / min.
[0042] Preparation of SiC fiber preform: The SiC fiber braid with the interface layer deposited thereon is immersed in SiC@RE3Si2C2 impregnation slurry, and then dried to obtain a SiC@RE3Si2C2 fiber preform.
[0043] In an optional embodiment, the impregnation method of the SiC fiber braid includes vacuum impregnation, vibration impregnation, pressure impregnation, ultrasonic impregnation, ultrasonic-assisted vacuum impregnation or vibration-assisted vacuum impregnation, preferably ultrasonic-assisted vacuum impregnation. More preferably, the impregnation time is 10 min to 3 h, preferably 10 min to 2 h.
[0044] In an optional embodiment, the drying method is atmospheric pressure drying or vacuum drying; depending on the solvent of the slurry, the drying temperature can be 40 to 90° C. and the drying time can be 5 to 20 hours.
[0045] The obtained SiC@RE3Si2C2 fiber preform is cut and stacked, and then placed in a hot pressing mold for hot pressing and sintering to obtain the NITE-SiC f / SiC ceramic matrix composite materials.
[0046] In an optional embodiment, the parameters of the hot pressing sintering include: a sintering temperature of 1300 to 1700°C, preferably 1300 to 1600°C; a sintering pressure of 5 to 50 MPa, and a sintering time of 0.5 to 4 hours. The present invention can achieve sintering density of the composite material while reducing damage to the fiber and interface through a hot pressing sintering process under appropriate conditions. Too high a sintering temperature, too high a sintering pressure, or too long a sintering time will damage the fiber and the interface; too low a sintering temperature, too low a sintering pressure, or too short a sintering time will result in insufficient sintering density.
[0047] In the present invention, the Archimedes drainage method is used to test the volume density and open porosity, and the three-point bending method is used to test the bending strength. f / SiC ceramic matrix composite material, the volume fraction of SiC fiber is 20-70%; the NITE-SiC f The volume density of SiC ceramic matrix composite material is 2.9~3.8g / cm 3 , the open porosity does not exceed 4%, and the flexural strength is 150-800MPa.
[0048] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0049] Example 1
[0050] The NITE-SiC provided in this embodiment 1 f The preparation method of the SiC ceramic matrix composite material comprises the following steps: (1) Preparation of SiC@Pr3Si2C2 powder of Pr3Si2C2 coated SiC. 74g SiC powder, 26g Pr powder, 224g KCl powder and 176g NaCl powder were placed in an agate mortar and mixed in a glove box for 20 minutes. The mixed powder was then poured into an alumina crucible and placed in a muffle furnace in the glove box. The temperature was raised to 900°C, kept warm for 5 hours, and then naturally cooled. The reacted powder was then dissolved in deionized water to remove the molten salt, ultrasonically dispersed, and then filtered. This operation was repeated 3 to 5 times until the filtered liquid could not discolor the silver nitrate solution. The filtered powder was vacuum dried in a vacuum drying oven at 60°C for 5 hours to obtain SiC@Pr3Si2C2 powder; (2) Preparation of SiC@Pr3Si2C2 impregnation slurry. 80g SiC@Pr3Si2C2 powder and 4g fish oil were placed in a ball mill, 252g anhydrous ethanol was added as a solvent, and the mixture was ball milled at a speed of 300r / min for 4h; then 15g polyvinyl butyral and 30g dibutyl phthalate were added, and the ball milling was continued for 12h to obtain SiC@Pr3Si2C2 impregnation slurry; (3) Weaving and interface deposition of SiC fibers. 6 g of SiC fibers were wound around a graphite mold to obtain a SiC fiber braid. The SiC fiber braid was then placed in a tubular furnace, and NH3, BCl3 and H2 were introduced. A BN interface layer was deposited on the surface of the SiC fiber by chemical vapor deposition at 810°C and 3 kPa. The flow rates of NH3, BCl3 and H2 were 50 mL / min, 15 mL / min and 200 mL / min, respectively, and the deposition time was 2 h. The thickness of the resulting BN interface layer was about 600 nm. (4) Preparation of SiC@Pr3Si2C2 fiber preform. The SiC fiber braid with the interface layer deposited in step (3) is immersed in the SiC@Pr3Si2C2 impregnation slurry obtained in step (2), and then evacuated and placed in an ultrasonic pot for ultrasonic-assisted vacuum impregnation for 2 hours. The vacuum-impregnated SiC fiber braid is placed in an oven and dried at 70°C for 10 hours to obtain a SiC@Pr3Si2C2 fiber preform; (5) The SiC@Pr3Si2C2 fiber preform obtained in step (4) is cut into a specific size and stacked in a hot pressing mold, and sintered at 1650°C and 15MPa for 2h to obtain SiC f / SiC ceramic matrix composite materials.
[0051] After testing, it can be seen that the SiC prepared in Example 1f In the SiC / SiC ceramic matrix composite material, the volume fraction of SiC fiber is 34%, f The volume density of the SiC ceramic matrix composite is 3.41±0.06g / cm 3 , the open porosity is 0.7±0.5%, and the flexural strength is 421.2±86.4MPa.
[0052] Example 2
[0053] The NITE-SiC provided in this embodiment 2 f The preparation method of the SiC ceramic matrix composite material comprises the following steps: (1) Preparation of SiC@Pr3Si2C2 powder of Pr3Si2C2 coated SiC. In a glove box, take 67g SiC powder, 33g Pr powder, 224g KCl powder and 176g NaCl powder and mix them in an agate mortar for 20 minutes. Then pour the mixed powder into an alumina crucible and place it in a muffle furnace in the glove box. Heat it to 900°C, keep it warm for 5 hours, and then cool it naturally. Then dissolve the reacted powder with deionized water to remove the molten salt, ultrasonically disperse it, and then filter it. Repeat this operation 3 to 5 times until the filtered liquid can no longer discolor the silver nitrate melt. The filtered powder is vacuum dried in a vacuum drying oven at 60°C for 5 hours to obtain SiC@Pr3Si2C2 powder; (2) Preparation of SiC@Pr3Si2C2 impregnation slurry. 80g SiC@Pr3Si2C2 powder and 4g fish oil were placed in a ball mill, 252g anhydrous ethanol was added as a solvent, and the mixture was ball milled at a speed of 300r / min for 4h; then 15g polyvinyl butyral ester and 30g dibutyl phthalate were added, and the ball milling was continued for 12h to obtain SiC@Pr3Si2C2 impregnation slurry; (3) Weaving and interface deposition of SiC fibers. 6 g of SiC fibers were wound around a graphite mold to obtain a SiC fiber braid. The SiC fiber braid was then placed in a tubular furnace, and NH3, BCl3 and H2 were introduced. A BN interface layer was deposited on the surface of the SiC fiber by chemical vapor deposition at 810°C and 3 kPa. The flow rates of NH3, BCl3 and H2 were 50 mL / min, 15 mL / min and 200 mL / min, respectively, and the deposition time was 2.5 h. The thickness of the resulting BN interface layer was about 800 nm. (4) Preparation of SiC@Pr3Si2C2 fiber preform. The fiber braid with the interface layer deposited in step (3) is immersed in the SiC@Pr3Si2C2 impregnation slurry obtained in step (2), and then evacuated and placed in an ultrasonic pot for ultrasonic-assisted vacuum impregnation for 2 hours. The SiC fiber braid after vacuum impregnation is placed in an oven and dried at 70°C for 10 hours to obtain a SiC@Pr3Si2C2 fiber preform; (5) The SiC@Pr3Si2C2 fiber preform obtained in step (4) is cut into a specific size, stacked vertically in a hot pressing mold, and sintered at 1550°C and 25MPa for 2h to obtain SiC f / SiC ceramic matrix composite materials.
[0054] After testing, it can be seen that the SiC prepared in Example 2 f In the SiC / SiC ceramic matrix composite material, the volume fraction of SiC fiber is 37%, f The volume density of the SiC ceramic matrix composite is 3.76±0.08g / cm 3 , the open porosity is 1.6±0.8%, and the flexural strength is 341.1±28.4MPa.
[0055] Example 3
[0056] The NITE-SiC provided in this embodiment 3 f The preparation method of the SiC ceramic matrix composite material comprises the following steps: (1) Preparation of SiC@Gd3Si2C2 powder of Gd3Si2C2 coated SiC. 72g SiC powder, 28g Gd powder, 224g KCl powder and 176g NaCl powder were placed in an agate mortar and mixed in a glove box for 20 minutes. The mixed powder was then poured into an alumina crucible and placed in a muffle furnace in the glove box. The temperature was raised to 950°C, kept warm for 5 hours, and then naturally cooled. The reacted powder was then dissolved in deionized water to remove the molten salt, ultrasonically dispersed, and then filtered. This operation was repeated 3 to 5 times until the filtered liquid could not discolor the silver nitrate solution. The filtered powder was vacuum dried in a vacuum drying oven at 60°C for 5 hours to obtain SiC@Gd3Si2C2 powder; (2) Preparation of SiC@Gd3Si2C2 impregnation slurry. 80 g SiC@Gd3Si2C2 powder and 4 g fish oil were placed in a ball mill, and 252 g anhydrous ethanol was added as a solvent. The mixture was ball milled at a speed of 300 r / min for 4 h. Then, 15 g polyvinyl butyral and 30 g dibutyl phthalate were added, and the ball milling was continued for 12 h to obtain SiC@Gd3Si2C2 impregnation slurry. (3) Weaving and interface deposition of SiC fibers. 6 g of SiC fibers were wound around a graphite mold to obtain a SiC fiber braid. The SiC fiber braid was then placed in a tubular furnace, and NH3, BCl3 and H2 were introduced. A BN interface layer was deposited on the surface of the SiC fiber by chemical vapor deposition at 810°C and 3 kPa. The flow rates of NH3, BCl3 and H2 were 50 mL / min, 15 mL / min and 200 mL / min, respectively, and the deposition time was 3.5 h. The thickness of the resulting BN interface layer was about 1000 nm. (4) Preparation of SiC@Gd3Si2C2 fiber preform. The fiber braid with the interface layer deposited in step (3) is immersed in the SiC@Gd3Si2C2 impregnation slurry obtained in step (2), and then evacuated and placed in an ultrasonic pot for ultrasonic-assisted vacuum impregnation for 2 hours. The SiC fiber braid after vacuum impregnation is placed in an oven and dried at 70°C for 10 hours to obtain a SiC@Gd3Si2C2 fiber preform; (5) The SiC@Gd3Si2C2 fiber preform in step (4) is cut into a specific size, placed in a hot pressing mold, and sintered at 1700°C and 20MPa for 2h to obtain SiC f / SiC ceramic matrix composite materials.
[0057] After testing, it can be seen that the SiC prepared in Example 3 f In the SiC / SiC ceramic matrix composite material, the volume fraction of SiC fiber is 51%, SiC f The volume density of the SiC ceramic matrix composite is 3.48±0.04g / cm 3 , the open porosity is 2.5±0.4%, and the flexural strength is 446±127.2MPa.
[0058] Comparative Example 1
[0059] In this comparative example 1, NITE-SiC f The preparation process of the SiC / SiC ceramic matrix composite material is similar to that of Example 1, except that in step (3), the deposition time of the BN interface layer is 20 min.
[0060] It can be seen from the test that the SiC prepared in this comparative example 1 f In the SiC ceramic matrix composite material, the material exhibits the characteristics of brittle fracture. f The flexural strength of the SiC ceramic matrix composite material is only 231±65MPa.
[0061] Comparative Example 2
[0062] In this comparative example 2, NITE-SiC fThe preparation process of the SiC / SiC ceramic matrix composite material is similar to that of Example 1, except that in step (5), the sintering temperature is 1800°C.
[0063] It can be seen from the test that the SiC prepared in this comparative example 2 f In SiC / SiC ceramic matrix composites, SiC f The volume density of the SiC ceramic matrix composite is 3.42±0.21g / cm 3 The open porosity is 3.6±0.4%, the flexural strength is only 271±25MPa, and it shows brittle fracture characteristics.
[0064] Figure 1 The morphology of SiC@Pr3Si2C2 powder of Pr3Si2C2 coated SiC prepared by the present invention is shown in the figure. As can be seen from the figure, Pr3Si2C2 powder grows on the surface of SiC grains in the form of lamellae.
[0065] Figure 2 Preparation of NITE-SiC for Example 1 of the present invention f The SEM image of the polished cross-section of the NITE-SiC ceramic matrix composite material. f / SiC composite materials fibers and interfaces are intact.
[0066] Figure 3 NITE-SiC prepared in Example 1 of the present invention f Load-displacement curve of NITE-SiC ceramic matrix composite material. As can be seen from the figure, the NITE-SiC prepared in Example 1 of the present invention f / SiC ceramic matrix composites exhibit pseudo-plastic fracture behavior.
[0067] Figure 4 NITE-SiC prepared in Example 1 of the present invention f XRD pattern of NITE-SiC ceramic matrix composite material. f / SiC ceramic matrix composite materials are composed of highly crystallized SiC and Pr2O3.
[0068] Figure 5 NITE-SiC prepared in Comparative Example 2 f SEM image of the polished cross-section of the SiC ceramic matrix composite material. As can be seen from the image, the high-temperature material fiber and interface are corroded, and the metal erodes into the fiber interface, resulting in a decrease in strength.
[0069] Figure 6 NITE-SiC prepared in Comparative Example 2 fLoad-displacement curve of SiC ceramic matrix composite material. As can be seen from the figure, the high-temperature fiber is corroded, which reduces its strength and shows brittle fracture characteristics.
Claims
1. A NITE-SiC f A method for preparing a SiC ceramic matrix composite material, comprising: The NITE-SiC is prepared by powder preparation, SiC fiber weaving, slurry impregnation and hot pressing sintering. f / SiC ceramic matrix composite material, characterized by: The powder is prepared by: in-situ growing a RE3Si2C2 coating layer on the surface of SiC powder by a molten salt method to obtain SiC@RE3Si2C2 powder of SiC coated with RE3Si2C2; the molten salt method comprises: taking a rare earth metal element powder or a rare earth metal hydride as a raw material, mixing it with SiC powder and molten salt, and synthesizing it to obtain the SiC@RE3Si2C2 powder of SiC coated with RE3Si2C2; The slurry impregnation is as follows: SiC@RE3Si2C2 powder is mixed with a mixed solution to prepare SiC@RE3Si2C2 impregnation slurry, and then the SiC fiber braid is immersed in the SiC@RE3Si2C2 impregnation slurry.
2. The preparation method according to claim 1, characterized in that: The rare earth metal single substance powder is at least one of Pr powder, Gd powder, Y powder and Ho powder; The rare earth metal hydride is at least one of PrH3, GaH2, and YH2; The molten salt is at least two of NaCl, KCl, LiCl, Na2SO4, and K2SO4; preferably, the molten salt is mixed in an atomic ratio of 1:1; The synthesis temperature of the molten salt method is 750-1100° C. and the time is 2-10 hours.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the rare earth metal single substance powder or rare earth metal hydride is 0.5 to 500 μm; the particle size of the SiC powder is 40 to 10000 nm; the thickness of the RE3Si2C2 coating layer is 10 to 2000 nm; the total particle size of the SiC@RE3Si2C2 powder is 50 to 12000 nm; Preferably, the atomic ratio of the rare earth metal element powder or rare earth metal hydride to SiC powder is 1:(2-25).
4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the total mass of the rare earth metal powder or rare earth metal hydride and SiC powder to the mass of the molten salt is 1:(3-8).
5. The preparation method according to any one of claims 1 to 4, characterized in that: The SiC@RE3Si2C2 powder is mixed with a mixed solution to obtain a SiC@RE3Si2C2 impregnation slurry; wherein the mixed solution comprises a dispersant, a binder, a plasticizer and a solvent; Preferably, the dispersant is polyvinyl pyrrolidone, polyethylene imine, tetramethyl ammonium hydroxide, fish oil or castor oil; the binder is polyvinyl butyral or polyvinyl alcohol; the plasticizer is polyethylene glycol, dibutyl phthalate or butyl benzyl phthalate; the solvent is deionized water, anhydrous ethanol, xylene or isopropanol; Preferably, the mass ratio of the SiC@RE3Si2C2 powder, dispersant, binder, plasticizer and solvent is 1: (0.01-0.1): (0.01-0.2): (0.005-0.5): (2-10); more preferably, it is 1: (0.01-0.1): (0.01-0.1): (0.005-0.25): (2-10).
6. The preparation method according to any one of claims 1 to 5, characterized in that: SiC fibers are braided to obtain the SiC fiber braid; preferably, the SiC fibers are continuous SiC fibers with a diameter of 5 to 20 μm; more preferably, the SiC fibers are braided in a unidirectional winding, 2D braiding, 2.5D braiding or 3D braiding manner.
7. The preparation method according to any one of claims 1 to 6, characterized in that The interface layer is deposited on the surface of the SiC fiber braid by chemical vapor deposition; wherein the interface layer includes a single-layer interface phase or a multi-layer interface phase; preferably, the single-layer interface phase is at least one of a pyrolytic carbon interface, a BN interface, and a SiC interface; the multi-layer interface phase is (PyC-SiC) n 、(BN-SiC) n 、(BN-PyC) n At least one of; More preferably, the thickness of the interface layer is 100 to 1500 nm; Preferably, the conditions of the chemical vapor deposition method include: a deposition temperature of 800 to 1300° C., a gas pressure of 1 to 30 kPa, and a deposition time of 0.5 to 5 h; depending on the type of interface layer, the reaction gas includes methane, ethane, ethylene, propylene, boron trichloride, ammonia, methyltrichlorosilane, and the flow rate is 5 to 50 mL / min; the dilution gas and carrier gas are hydrogen or argon hydrogen, and the flow rate is 50 to 200 mL / min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The SiC fiber braid is immersed in the SiC@RE3Si2C2 impregnation slurry, and dried to obtain a SiC@RE3Si2C2 fiber preform; the impregnation method of the SiC fiber braid includes vacuum impregnation, vibration impregnation, pressure impregnation, ultrasonic impregnation, ultrasonic-assisted vacuum impregnation or vibration-assisted vacuum impregnation; the impregnation time is 10 min to 3 h, preferably 10 min to 2 h; The drying method is atmospheric pressure drying or vacuum drying; preferably, the drying temperature is 40 to 90° C. and the drying time is 5 to 20 hours.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The SiC@RE3Si2C2 fiber preform is laminated and hot-pressed to obtain the NITE-SiC f / SiC ceramic matrix composites; The parameters of the hot pressing sintering include: a sintering temperature of 1300-1700° C., a sintering pressure of 5-50 MPa, and a sintering time of 0.5-4 h.
10. A NITE-SiC prepared by the preparation method according to claims 1-9 f / SiC ceramic matrix composite material, characterized in that The NITE-SiC f / In SiC ceramic matrix composite materials, the volume fraction of SiC fiber is 20-70%; The NITE-SiC f The volume density of SiC ceramic matrix composite material is 2.9~3.8g / cm 3 ; The NITE-SiC f The open porosity of the SiC ceramic matrix composite material does not exceed 4%, preferably does not exceed 3%; The NITE-SiC f The flexural strength of SiC ceramic matrix composite materials is 150-800 MPa.